THE IMPACT OF PUBLIC FINANCIAL LITERACY ON THE REAL ESTATE MARKET IN THE USA AND UKRAINE - Vlasova, Mariya (SWorldJournal, 2025)
The article explores how financial literacy among the population affects the functioning of the real estate market in the USA and Ukraine, with a particular focus on the role of public awareness in shaping investment behavior and decision-making within di